Possessions: Indigenous Art / Colonial Culture - Thomas, Nicholas (Interplay, arts, history, theory, 1999)
Tribal art has greatly inspired much 20th-century Western art. But is this a cross-cultural discovery to be celebrated, or another example of Western colonial appropriation? This work, focusing on countries such as Australia and New Zealand, argues that both views are too simplistic
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé